2015
DOI: 10.2991/icmra-15.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Internal Flowpath Optimization of Wet Multi-plate Friction Clutch

Abstract: The research about internal flowpath optimization of wet friction clutch has significant effect on the reduce of heat generating. Taking the diameter and position of nozzle as design parameters, the maximum and minimum lubricant pressure as constraint conditions, and the RMS of lubricant pressure applied on friction disc and dual plate as objective function, the parametric FEM optimum model of flowpath about clutch is established. Based on the method of second order response surface, the paper sets up the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…It was found that the method used in this work was able to give a convenient and cost effective measurement of friction coefficients and their transitions of a clutch facing material. The obtained results will be useful for the development process of new facing materials Flowpath Optimization of Wet Multi-plate Friction Clutch By Qing Wang, Tengjiao Lin , Li Pan and Quancheng Peng [9] explained that by optimizing internal flow path of wet friction clutch heat generated can be reduced significantly. The optimized structure of flow path is obtained, and the rationality of optimization result is verified.…”
Section: Introductionmentioning
confidence: 96%
“…It was found that the method used in this work was able to give a convenient and cost effective measurement of friction coefficients and their transitions of a clutch facing material. The obtained results will be useful for the development process of new facing materials Flowpath Optimization of Wet Multi-plate Friction Clutch By Qing Wang, Tengjiao Lin , Li Pan and Quancheng Peng [9] explained that by optimizing internal flow path of wet friction clutch heat generated can be reduced significantly. The optimized structure of flow path is obtained, and the rationality of optimization result is verified.…”
Section: Introductionmentioning
confidence: 96%